Reliability of the pressure indicating film for occlusal force analysis: a pilot study/ Idris RI ... [et al.] - RI, Idris; NI, Tasri; SF, Yusof; TW, Lim; Y, Shoji (2019)
Objective: : The aim of this study was to evaluate the reliability of the pressure indicating film in measuring pressure exerted on it with and without Polyethylene (PE) sleeve as infection control purposes, and to analyze the pressure produced with its software for occlusal force study. Materials and Methods: The optimization of the pressure indicating film for occlusal force analysis commenced with the design and calibration of this sheet. The film was designed into horseshoe shape to suit the shape of maxillary and mandibular arches. The calibration was initiated with 5 different types of pressure which were 15 MPa, 25 MPa, 30 MPa, 35 MPa and 45 MPa exerted on two groups of the film: (i) with PE sleeve and (ii) without PE sleeve. Three readings were recorded for each group and mean value was documented. Then, the films were calibrated by its software for pressure analysis. Results: There was no significance difference found between the film with and without PE sleeve during the calibration stage (P>0.05). In all groups of pressure, there was no significant difference documented between pressure exerted and read out value. Conclusion: The results suggested that the film can be used for occlusal force analysis and improvement of the film with addition of PE sleeve for hygienic purpose is suitable to form the basis of clinical occlusal forces study.